The Prevalence, Risk Factors, and Outcomes of Sepsis in Critically Ill Patients in China: A Multicenter Prospective Cohort Study - Wang, Meiping; Jiang, Li; Zhu, Bo; Li, Wen; Du, Bin; Kang, Yan; Weng, Li; Qin, Tiehe; Ma, Xiaochun; Zhu, Duming; Wang, Yushan; Zhan, Qingyuan; et al. (Frontiers in Medicine, 2020)
Background: Sepsis is a main cause of morbidity and mortality in critically ill patients. The epidemiology of sepsis in high-income countries is well known, but information on sepsis in middle- or low-income countries is still deficient, especially in China. The purpose of this study was to explore the prevalence, characteristics, risk factors, treatment and outcomes of sepsis in critically ill patients in tertiary hospitals in China. Methods: A multicentre prospective observational cohort study was performed with consecutively collected data from adults who stayed in any intensive care unit (ICU) for at least 24 hours; data were collected from 1 January 2014 to 31 August 2015, and patients were followed until death or discharge from the hospital. Results: A total of 4910 patients were enrolled in the study. Of these, 2086 (42.5%) presented with sepsis or septic shock on admission to the ICU or within the first 48 hours after admission to the ICU. ICU mortality was higher in patients with sepsis (13.1%) and septic shock (39.0%) and varied according to geographical region. Acinetobacter, Pseudomonas and Staphylococcus infections were associated with increased ICU mortality. In addition, age, Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, pre-existing cardiovascular diseases, malignant tumours, renal replacement therapy (RRT) and septic shock were independent risk factors for mortality in patients with sepsis. The prompt administration of antibiotics (OR 0.65, 95% CI 0.46-0.92) and 30 mL/kg of initial fluid resuscitation during the first 3 hours (OR 0.43, 95% CI 0.30-0.63) improved the outcome in patients with septic shock. Conclusions: Sepsis was common and was associated with a high mortality rate in critically ill patients in tertiary hospitals in China. The prompt administration of antibiotics and 30 mL/kg fluid resuscitation decreased the risk of mortality.